2020
DOI: 10.1136/bmjdrc-2019-001125
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and perspectives of the parents of emerging adults living with type 1 diabetes

Abstract: IntroductionWhereas it is widely recognized that emerging adulthood can be a difficult time in the life of an individual living with type 1 diabetes, relatively little is known about the experiences of their parents or guardians. These individuals once shouldered much of the burden for their child’s diabetes ‘self’-management, yet their contribution is often overlooked by the adult healthcare system. Here, we set out to gain an understanding of the perspectives of parents of emerging adults living with type 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 33 publications
(35 reference statements)
2
22
0
Order By: Relevance
“…27 Other studies highlighted the discomfort of parents in 'stepping back' and the lack of support they themselves felt from the medical system as their children aged. 5,28 Although our adolescent participants emphasized the desire to gradually take over diabetes management from their parents as they grew older, they also identified that the ideal relationship with their parents was one of support and teamwork rather than complete separation, as is consistent with other research. 3 Our findings highlight the complexity of the changing adolescent-parent relationship and the importance of providing guidance not just to adolescents but also to their parents, on how to adopt mutually supportive roles during the transition process.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…27 Other studies highlighted the discomfort of parents in 'stepping back' and the lack of support they themselves felt from the medical system as their children aged. 5,28 Although our adolescent participants emphasized the desire to gradually take over diabetes management from their parents as they grew older, they also identified that the ideal relationship with their parents was one of support and teamwork rather than complete separation, as is consistent with other research. 3 Our findings highlight the complexity of the changing adolescent-parent relationship and the importance of providing guidance not just to adolescents but also to their parents, on how to adopt mutually supportive roles during the transition process.…”
Section: Discussionsupporting
confidence: 78%
“…One study showed parents' reluctance for their adolescents to have clinic visits alone with their paediatric endocrinologists, fearing loss of information and ability to provide support 27 . Other studies highlighted the discomfort of parents in ‘stepping back’ and the lack of support they themselves felt from the medical system as their children aged 5,28 . Although our adolescent participants emphasized the desire to gradually take over diabetes management from their parents as they grew older, they also identified that the ideal relationship with their parents was one of support and teamwork rather than complete separation, as is consistent with other research 3 .…”
Section: Discussionsupporting
confidence: 76%
“…The strengths of the study include the prolonged duration of follow-up, the focus on the provision of care to emerging adults with type 1 diabetes during the pandemic, and the previous characterization of this clinic population [ 19 , 20 , 22 ]. Limitations include its retrospective, single-centre nature.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of parents on emerging adults with health conditions (eg, eating disorders, 42 cancer, 43 drug use, 44 and diabetes 45 ) has been well‐described, especially in the context of nursing research 21 . Most recent research on emerging adulthood has highlighted the impact of parents on health behaviors in Korean university students during the COVID‐19 global pandemic (eg, following lockdown regulations, social distancing, etc) 46 .…”
Section: Aim Of the Reviewmentioning
confidence: 99%